A novel technique for implementing reactance in spin domain using Spin Hall Effect. (September 2018) - Chattopadhyay, Saranyu
Abstract: This paper shows how spin current can be manipulated using charge-based analog elements. The technique proposed in this paper transforms charge-based reactance to spin-based reactance using Spin Hall Effect (SHE) and Inverse Spin Hall Effect (ISHE) simultaneously. The charge current created by ISHE provides a feedback impedance to the spin channel via SHE. The conceived circuit is theoretically verified using the spin circuit model. This technique holds great potential for realization of spin based analog devices like spin capacitors and spin inductors.